Agreeing peace in Colombia or ‘the very thing’ of philosophy - Chaparro Amaya, Adolfo (Estudios de Filosofía, 2018)
This article aims to make a philosophical reading of the peace agreements signed between the Colombian government and the FARC guerrilla. After (i) presenting Derrida’s thesis about the need to deconstruct the concept of the enemy as the very thing of philosophy, and (ii) attempting an approach to the concepts of reconcilement and re–evolution in the different fields of the conflict, then, (iii) I return to the initial thesis in order to suggest exploration routes by way of theoretical indications on how to re-signify the concept of enemy in terms of a genuine social and philosophical pluralism.